Effects of polystyrene microplastic on uptake and toxicity of copper and cadmium in hydroponic wheat seedlings (Triticum aestivum L.) - Zong, Xueying; Zhang, Juanjuan; Zhu, Jinwei; Zhang, Linyu; Jiang, Lijuan; Yin, Ying; Guo, Hongyan (Ecotoxicology and environmental safety, 2021)
Microplastics are widespread in freshwater environments, their biological effects and combined effects of other pollutants have attracted extensive attention. In this study, we investigated the adsorption properties of heavy metals onto polystyrene (PS) microplastics as well as the bioavailability and toxicity of microplastics and heavy metals by hydroponic wheat seedlings experiment. Results showed that PS microplastics (0.5 µm, 100 mg/L) had no significant effect on wheat seedlings growth, photosynthesis, and reactive oxygen species (ROS) content. However, PS microplastics could adsorb copper and cadmium, with a predominantly chemisorption. The accumulation of copper and cadmium in wheat seedlings reduced in the presence of PS microplastics, which meant the toxic effect by heavy metals might be mitigated. Compared with single heavy metals treatments, the combination of PS microplastics and heavy metals increased chlorophyll content, enhanced photosynthesis and reduced the accumulation of ROS. These findings suggest that PS microplastics (0.5 µm, 100 mg/L) have a mitigating effect on the bioavailability and toxicity of copper and cadmium. [Display omitted] •PS microplastics (0.5 μm, 100 mg/L) had no significant effect on wheat seedlings.•Adsorption kinetics of Cu2+ and Cd2+ onto PS microplastics were fitted well by the pseudo-second-order model.•The accumulation of metals in wheat seedlings decreased by the presence of PS microplastics.•PS microplastics had a mitigating effect on the toxicity of copper and cadmium.